Multidisciplinary approach to patients with post-stroke dysphagia to improve swallowing and quality of life - Xu Bu; Rong Xiangxia; Gan Yan; Wei Tao; Zhang Xiufang; Liu Jingjing; Zhang Jing; Wang Zilin (Srpski Arhiv za Celokupno Lekarstvo, 2025)
Introduction/Objective. Inflammatory bowel disease (IBD) is often diagnosed during patients’ sexually active years, and factors like disease severity, treatment, and surgery may impact sexual function. This study aimed to assess the sexual quality of life in IBD patients. Methods. Patients with IBD and control groups (n = 45) were prospectively included in this study. Demographic data of patients and duration of illness, laboratory and endoscopic data, and treatment information were recorded. Participants completed the Patient-Reported Outcomes Measurement Information System (PROMIS) Sexual Activity Index. Results. In total, 103 patients were included (41 patients with ulcerative colitis and 17 patients with Crohn’s disease). The mean age of patients with IBD was 34.26 ± 10.1 years, while the control group had a mean age of 32.93 ± 10.5 years (p = 0.518). The mean total PROMIS was found to be lower in the patient group (men: 29.8 ± 7.4; women: 28.1 ± 7.7) than in the control group (men: 38.5 } 5.4; women: 34.8 ± 11.6), but the difference was statistically significant only in men (p < 0.001). The median value of the Sexual Life Quality Index was found to be lower in the patient group [men: 3 (1–5); women: 3 (1–4)] than in the control group [men: 5 (3–5); women: 4 (1–5)]. The low Sexual Life Quality Index difference was significant in both men (p < 0.001) and women (p = 0.042). Conclusion. IBD patients showed lower sexual quality of life compared to the general population. Assessing sexual well-being alongside disease activity may positively impact disease management.